(untitled) (Medical Forum Monthly, 2024)
Objective: The purpose of this study was to investigate the possible role of Cyanacobalamin (Vitamin B-12) in reducing the hazardous effects of heat on seminiferous tubules of testes in albino rats. Study Design: Experimental Study Place and Duration of Study: This study was conducted in the Department of Anatomy, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi, for 6 weeks from October 2010 to November 2010. Materials and Methods: Thirty adult albino rats of 200-250 grams of weight and 90-120 days of age were taken for this study. They were divided into three groups A (control), B (heat treated), and C (heat plus Cyanocobalamin treated). They were further subdivided into A1&A2, B1&B2 and C1&C2, based on duration of treatment of 4 weeks and 6 weeks respectfully. At the end of study histological examination of seminiferous tubules of testes were seen by applying Periodic Acid Schiff Iron Hematoxylin stain. Results: There was marked damaging effects of heat (420C) on seminiferous tubules of testes with disorganized germinal epithelium and vacuolation. This damage to spermatogenic cell series was well protected with concomitant treatment with Cyanacobalamin (vitamin B-12). There was restoration of germinal epithelium and marked decrease in vacuolation. Conclusion: This study proved protective role of Cyanacobalmin (Vitamin B-12) in heat induced damage in testes of albino rats.